PERSPECTIVE OF GENERASI Z FASHION AS MANIFESTATION OF SOCIAL CONSTRUCTIONISM - Ananta, Dede; Falah, Asep Miftahul (Universitas Ciputra Surabaya, 2023)
This study explores Generation Z's view of fashion as a manifestation of social constructionism. This research attempts to answer questions about how Generation Z understands and responds to fashion trends and how fashion trends play a role in the social construction of their identities. The research problem studied is the role of fashion in shaping self-perception and how social views influence the acceptance and interpretation of fashion trends by Generation Z. The basic design of this study uses qualitative methods with a phenomenological approach. Data was collected through observation and distribution of questionnaires with several participants from Generation Z, who represented various social and cultural backgrounds. The collected data is then analyzed thematically to identify key trends and emerging findings. The analysis shows that Generation Z sees fashion as a means to express their identity and build a social image with community groups. Fashion for them is not only about personal style but also a form of expression of their culture and social values. The main trend found is that Generation Z tends to be more inclusive and accepting of differences in fashion, rejecting stereotypes and rigid social norms. The interpretation of the results of this study shows that fashion for Generation Z is not just a tool to follow trends, but also a form of self-expression and social identity. In addition, they tend to reject social boundaries and fight for inclusivity in fashion.